Quartzite procurement not only in fluvial deposits: Raw material characterisation of the lithic assemblage from level XXII-R at El Esquilleu, Cantabrian Region, Spain. (2021) - Prieto, Alejandro; Yusta, Iñaki; Garcia-Rojas, Maite; Arrizabalaga, Alvaro; Preysler, Javier Baena
No abstract available